Komunikasi Bahasa Indonesia sebagai Pemersatu Bangsa - Efendi, Erwan; Akbar, Rizky Akbar; Sahlaya, Muhammad Rishan; Tadjuddin, Asri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Humans are social beings who interact with each other. The form of this interaction can be reflected in the form of communication. Communication is used to convey certain intentions from one person to another through language, be it verbal, written or sign language. Without language, it will be difficult for us to convey our intentions or goals to others and to establish relationships in everyday life. This study uses a qualitative method, namely where reference sources are obtained from literature studies originating from articles, journals, opinions of experts and researchers who first examine Indonesian language communication which is used as a unifying nation. Keywords: Communication, Indonesian and Unifying Language.